Designing and evaluating a patient decision aid for patients with locally advanced or locally recurrent rectal cancer: a national multicentre mixed methods study protocol. Issue 6 (15th June 2022) - Williams, Anwen; Hutchings, Hayley Anne; Harris, Dean Anthony; Evans, Martyn; Harji, Deena
Abstract : Introduction: Approximately 5%–10% of new rectal cancers are locally advanced (locally advanced rectal cancer (LARC)) at presentation with 4%–8% recurring (locally recurrent rectal cancer (LRRC)) after initial treatment. Patients with potentially curable disease have to consider many trade-offs when considering major exenterative surgery. There are no decision tools for these patients and current resources have found to not meet minimum international standards. The overall aim of this study is to produce a validated patient decision aid (PtDA) to assist patients considering radical pelvic exenteration for LARC and LRRC created in line with international minimum standards. Methods and analysis: This study is a national, multicentre mixed methods project and has been designed in keeping with guidance from the International Patient Decision Aids Standard. This study is in four stages. In stage 1, we will develop the PtDA and its content using agile developmental methodology. In stage 2, we will assess the content and face validity of the PtDA using mixed-methods with key stakeholders. In stage 3, we will assess the feasibility and efficacy of the PtDA. In stage 4, we will establish the barriers and facilitators to the use of a PtDA in the outpatient setting. Questionnaires including the QQ-10, EORTC PATSAT-C33, Preparation for Decision-Making Scale and the NoMAD survey will be analysed during the study. Interviews will be analysed using thematic analysis. Ethics and dissemination: Research ethics approval from North of Scotland Research Ethics Service 19/NS/0056 (IRAS 257890) has been granted. Results will be published in open access peer-reviewed journals, presented in conferences and distributed through bowel research UK charity. External endorsement will be sought from the International Patient Decision Standards Collaboration inventory of PtDAs. PROSPERO registration number: CRD42019122933.